The relationship of nursing home price and quality of life - Sarah Raes; Sophie Vandepitte; Delphine De Smedt; Herlinde Wynendaele; Yannai DeJonghe; Jeroen Trybou (BMC, 2020)
Abstract Background Knowledge about the relationship between the residents' Quality of Life (QOL) and the nursing home price is currently lacking. Therefore, this study investigates the relationship between 11 dimensions of QOL and nursing homes price in Flemish nursing homes. Methods The data used in this cross-sectional study were collected by the Flemish government from years 2014 to 2017 and originates from 659 Flemish nursing homes. From 2014 to 2016, data on the QOL of 21,756 residents was assessed with the InterRAI instrument. This instrument contains 11 QOL dimensions. Multiple linear regression analyses were conducted to examine the research question. Results The multiple linear regressions indicated that a 10 euro increase in the daily nursing home price is associated with a significant decrease (P <  0.001) of 0.1 in 5 dimensions of QOL (access to services, comfort and environment, food and meals, respect, and safety and security). Hence, our results indicate that the association between price and QOL is very small. When conducting a subgroup analysis based on ownership type, the earlier found results remained only statistically significant for private nursing homes. Conclusion Our findings show that nursing home price is of limited importance with respect to resident QOL. Contrary to popular belief, our study demonstrates a limited negative effect of price on QOL. Further research that includes other indicators of QOL is needed to allow policymakers and nursing home managers to improve nursing home residents' QOL.